2017
DOI: 10.1158/2159-8290.cd-17-0716
|View full text |Cite
|
Sign up to set email alerts
|

Early Detection of Molecular Residual Disease in Localized Lung Cancer by Circulating Tumor DNA Profiling

Abstract: Identifying molecular residual disease (MRD) after treatment of localized lung cancer could facilitate early intervention and personalization of adjuvant therapies. Here, we apply cancer personalized profi ling by deep sequencing (CAPP-seq) circulating tumor DNA (ctDNA) analysis to 255 samples from 40 patients treated with curative intent for stage I–III lung cancer and 54 healthy adults. In 94% of evaluable patients experiencing recurrence, ctDNA was detectable in the fi rst posttreatment blood sample, indica… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

31
675
3
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 781 publications
(756 citation statements)
references
References 33 publications
31
675
3
5
Order By: Relevance
“…Quarterly ctDNA testing yielded a similar lead time of 150 days because of our assumption that imaging is performed at the same frequency. These predicted lead times for early stage lung cancer are similar to the reported median of ~160 days by Chaudhuri et al (Chaudhuri et al 2017) and slightly longer than the reported median of 70 days (range, 10 -346 days) by Abbosh et al (2017), likely due to less frequent relapse testing and a lower average number of clonal mutations covered by the sequencing panel (range 3-26).…”
Section: Tumor Relapse Detection If Mutations Are Known a Priorisupporting
confidence: 86%
“…Quarterly ctDNA testing yielded a similar lead time of 150 days because of our assumption that imaging is performed at the same frequency. These predicted lead times for early stage lung cancer are similar to the reported median of ~160 days by Chaudhuri et al (Chaudhuri et al 2017) and slightly longer than the reported median of 70 days (range, 10 -346 days) by Abbosh et al (2017), likely due to less frequent relapse testing and a lower average number of clonal mutations covered by the sequencing panel (range 3-26).…”
Section: Tumor Relapse Detection If Mutations Are Known a Priorisupporting
confidence: 86%
“…Conventional PCR amplification is useful to confirm the presence of the fusion sequence and corresponding tumor cells, without the need for an allele‐specific or mutation‐specific amplification system mainly used in earlier studies; however, strict precautions are necessary to avoid any contaminations, which may result in false‐positive results. As reported previously, an assay using cfDNA has been proven to be useful for the early detection of tumor progression/recurrence. In the nested PCR analysis for the PAX3‐FOXO1 fusion using plasma cfDNA samples, the fusion sequence turned out to be detectable at the “remission stage,” when imaging analyses such as FDG‐PET scanning could not detect any recurrence of the tumor (Figures and B).…”
Section: Discussionmentioning
confidence: 86%
“…Molecular characterization of circulating tumor DNA (ctDNA) is finding wide applications in cancer diagnostics and clinical decision-making including, but not limited to, early cancer detection (Phallen et al, 2017), tissue of origin classification (Kang et al, 2017), cancer genome characterization (Parikh et al, 2019), epigenetic profiling (Snyder et al, 2016), and cancer monitoring after treatment (Chaudhuri et al, 2017). Although analyzing cfDNA sequencing data do not conceptually differ from the 1 analysis of biopsy-based DNA sequencing, there are several details that require specialized bioinformatics tools.…”
Section: Introductionmentioning
confidence: 99%